APPLICATION OF PROCTORING TECHNOLOGIES IN MODERN EDUCATION - Muratuly, Didar (Вестник ВКТУ им. Д. Серикбаева, 2023)
The scientific article "The use of proctoring technologies in modern education" is a comprehensive analysis of modern approaches and trends in the use of proctoring technologies in educational institutions. In the light of dynamic changes in the educational process, especially in the context of the spread of distance learning, the relevance of effective methods of assessment and ensuring integrity becomes undeniable. The article covers a wide range of topics, including technical innovations in proctoring systems, the variability of methods (biometric data, audio and video surveillance, etc.), the ethical aspects of the use of such technologies, as well as the impact on the psychological aspect of learning and student outcomes.